2012
DOI: 10.1128/aem.01503-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Two Neurospora crassa Cellobiose Dehydrogenases and Their Connection to Oxidative Cellulose Degradation

Abstract: ABSTRACTThe genome ofNeurospora crassaencodes two different cellobiose dehydrogenases (CDHs) with a sequence identity of only 53%. So far, only CDH IIA, which is induced during growth on cellulose and features a C-terminal carbohydrate binding module (CBM), was detected in the secretome ofN. crassaand preliminarily characterized. CDH IIB is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
126
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 42 publications
(59 reference statements)
7
126
0
Order By: Relevance
“…The ascomycete CDHs isolated from N. crassa have a broader substrate spectrum and less glucose discrimination than basidiomycete CDHs (30). While basidiomycete CDHs catalyze the reactions at acidic pH, ascomycete CDHs are active at neutral or alkaline pH (41). Whether the differences in the biochemical characteristics of CDHs between basidiomycetes and ascomycetes are also valid for Aspergillus species remains to be clarified.…”
Section: Cellulose-degrading Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ascomycete CDHs isolated from N. crassa have a broader substrate spectrum and less glucose discrimination than basidiomycete CDHs (30). While basidiomycete CDHs catalyze the reactions at acidic pH, ascomycete CDHs are active at neutral or alkaline pH (41). Whether the differences in the biochemical characteristics of CDHs between basidiomycetes and ascomycetes are also valid for Aspergillus species remains to be clarified.…”
Section: Cellulose-degrading Enzymesmentioning
confidence: 99%
“…First, the ability of CDH to accept electrons from xylooligosaccharides and interact with various LPMOs was detected, suggesting that these enzymes are able to act on hemicelluloses (41). Recently, LPMO9C of the ascomycete fungus Neurospora crassa was shown to cleave xyloglucan, ␀-glucan, and, to a lesser extent, glucomannan with ascorbic acid as a reductant (40).…”
Section: Hemicellulose Degradationmentioning
confidence: 99%
“…Recent studies demonstrated that LPMOs act in concert with CDH since their association resulted in an increase in the conversion of cellulose, assuming a key role of this oxidative system in fungi (8,11,12,31). The effectiveness of LPMO/CDH synergy seems to depend on enzyme concentrations and the type of substrate used.…”
mentioning
confidence: 99%
“…Nevertheless, their actual function is still not fully understood (1,9,15,16). Recently, fungal CDHs were shown to act as a reductant for lytic polysaccharide mono-oxygenases (LPMOs), providing electrons for the redox-mediated oxidative cleavage of cellulose (14,17,(21)(22)(23). The electrons are rapidly transferred from the flavin to the heme domain of CDH via the heme propionate group (24)(25)(26).…”
mentioning
confidence: 99%
“…The first CDHs, initially named cellobiose oxidase, were discovered as enzymes able to catalyze the cellobiose-dependent reduction of quinones (5,6). Their enzymatic properties have been characterized in many fungi, including Phanerochaete chrysosporium (7), Trametes versicolor (8), Schizophyllum commune (9), Pycnoporus cinnabarinus (3), Pycnoporus sanguineus (10), Cerrena unicolor (11), Podospora anserina (12,13), and Neurospora crassa (14)(15)(16)(17). ZĂĄmockĂœ et al (18) divided the CDH family into three phylogenetic branches.…”
mentioning
confidence: 99%